2011
DOI: 10.3109/0142159x.2010.540594
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate ophthalmology education – A survey of UK medical schools

Abstract: Changes in the UK undergraduate medical curriculum mean that a clinical placement in ophthalmology is no longer a requirement. An ophthalmic assessment is necessary for a full physical examination and failure to elicit and interpret signs could mean missing sight and life-threatening pathology. This study was to investigate current undergraduate ophthalmology teaching. An email questionnaire, about the content and delivery of the ophthalmology teaching, was sent to each UK medical school in 2007/2008. The resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 15 publications
1
59
1
2
Order By: Relevance
“…2 However, in clinical practice, we have also found that this would not be necessary for the majority of patients. 3 In certain glaucoma patients, especially more advanced eyes, however, it is performed according to the judgment of the physician.…”
Section: Author Replymentioning
confidence: 95%
“…2 However, in clinical practice, we have also found that this would not be necessary for the majority of patients. 3 In certain glaucoma patients, especially more advanced eyes, however, it is performed according to the judgment of the physician.…”
Section: Author Replymentioning
confidence: 95%
“…The UK undergraduate medical curriculum no longer necessitates a clinical placement in ophthalmology (Baylis et al 2011). The General Medical Council's Tomorrow's Doctors documents on undergraduate medical education outcomes and clinical placements underline the importance of core clinical placements, of which an ophthalmic placement is not stipulated.…”
Section: Dear Sirmentioning
confidence: 99%
“…Over the past 30 years, the duration of the ophthalmology placement has dwindled in the United States, 1 the United Kingdom, 2 and elsewhere. 3 The inescapable truth is that without renewed activism from ophthalmologists interested in the education of tomorrow's doctors, 1 the ophthalmology clerkship-exposed by poor representation from ophthalmologists on medical school committees-may soon disappear entirely.…”
mentioning
confidence: 99%
“…3 The inescapable truth is that without renewed activism from ophthalmologists interested in the education of tomorrow's doctors, 1 the ophthalmology clerkship-exposed by poor representation from ophthalmologists on medical school committees-may soon disappear entirely. [1][2][3] The likely outcome is a generation of clinicians who lack confidence and competence in basic ophthalmic examination, 1 the management of simple eye complaints, and the safe triaging of patients under their care who develop serious ophthalmic disease. 4 Skills in direct ophthalmoscopy among undergraduates have declined in parallel.…”
mentioning
confidence: 99%